Dakwah pada Masyarakat Teknologi - Aep Kusnawan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2016)
Da'wah constantly faced the reality. Reality has a dynamic stance, turned and drove into the future. Analysis of the reality and the trend of future conditions are kenyaaan that all parties drove toward itu. One of the trend of the future is the development of increasingly complex technology. While each discovery technology has an influence on people. Where human at the same time is also the subject and the object of propaganda. So how propaganda in the technology community needs to be built? For this study trying to look into thinking propaganda of an expert in the field of technology and Muslim cendekiaan, Armahedi Mahzar. The results showed that, first, Thought propaganda Armahedi Mahzar not be separated from the socio hitoris life. Second, Armahedi views on the technology closely related to the shape of the philosophy behind the technology. Third, proselytizing view Armahedi in the technology community, stressed the need tazkiyatunnafs measures at the individual level; Patience and gratitude at the group level, asceticism and faqr at the community level, as well as the development of science based on Tawheed